Innovation and the Evolution of Industry Structure - Bloch, Harry (Routledge, 2018)
Â© 2018 Informa UK Limited, trading as Taylor & Francis Group. Great advances have been made in recent decades enriching the economic theory of innovation and in understanding the role innovation plays in the survival and success of businesses. Advances have also been made in theoretical and empirical research into the relationship between innovation and industry structure. In what follows I comment on these advances and point to areas in which more theoretical work might extend our understanding of the links between innovation and industry structure.